Pengaruh Permainan Mobile Edukasi Terhadap Proses Pembelajaran Berhitung Anak Tunagrahita Ringan - Wenda Novayani; Shumaya Resty Ramadhani; Irvandy Hartono (Universitas Hamzanwadi, 2021)
The difficulty of learning to count for Mentally Disabled Students (MDS) is not only because their intelligence is below the average of regular students and difficult to concentrate, but also because the material presented is less exciting and theoretical. The purpose of this study was to see the effect of the snake and ladder mobile game on the ability and speed of counting mentally disabled students in the process of count-learning. Data collection techniques in this study were interviews with teachers, User Accepted Test (UAT) questionnaires for measuring games, and research instruments in the form of summation essay questions. The research method used is an experiment with a one-group pre-test and post-test. The research subjects are four mentally disabled students at Pelita Hati Special School (SLB PH). Data analysis compares the score acquisition, the time it takes students to work on the questions during the pre-test and post-test, and UAT data analysis. The Results showed that this game made MDS interested in count-learning, improving learning outcomes, and increasing students' speed in learning counting at SLB PH compared with before playing this educational-game. Thus, the snake and ladder educational mobile game positively influences the count learning process of MDS.